Atomized measures and semiconvex compacta - Nykyforchyn, O.R. (Carpathian Mathematical Publications, 2010)
A class of atomized measures on compacta, which are generalizations of regular real-valued measures, is introduced. It has also been shown that the space of normalized (weakly) atomized measures on a compactum is a free object over this compactum in the category of (strongly) semiconvex compacta.